DROPOUT RATES AND RETENTION FACTORS OF A SINGLE-CENTRE WEIGHT MANAGEMENT CLINIC IN A TERTIARY HOSPITAL - Mohamad, Aimi Fadilah; Ismail, Zaliha; Hatta, Sharifah Faradila Wan Muhamad; Warman, Nuraini Eddy; Zainordin, Nur Aisyah; Awang, Mohd Hazriq; Shah, Fatimah Zaherah Mohamed; Ghani, Rohana Abdul (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Weight management clinics are the mainstay of obesity care in Malaysia. The UiTM weight management clinic comprises a 7-visit programme over a 1-year period involving various specialties such as primary care physicians, endocrinologist, nutritionist, psychologist, and rehabilitation medicine. Each provides different aspects of obesity management. There is a high dropout rate for this clinic, thus, it is essential to recognize those who will benefit from it. METHODOLOGY This is a retrospective analysis of 145 patients attending the weight management clinic in UiTM from June 2018 to December 2020. All data were acquired through patients’ medical records. Dropout rate is defined as the absence from 1 or more clinic visits at three monthly timepoints. Logistic regression analysis with SPSS version 22 was performed to identify factors predicting patients’ retention to the programme. RESULTS A total of 145 patients attended the clinic. Dropout rate at 3 months was 37% (n=53), cumulative rate at 6 months was 48% (n=70) and 59% (n=86) at 12 months. 59 patients (41%) completed the programme. Mean age was 39.1 ± 13.3 years and mean BMI 44.9 ± 10.2 kg/m2 . Patients with dyslipidemia comprised 75% of the cohort (n=109). Patients with a baseline body mass index (BMI) of >40 kg/ m2 and known dyslipidemia showed higher retention in the programme. Those with dyslipidaemia had a 4-fold increase in retention (OR 4.81 (CI 1.02,22.69)), p= 0.048) while those with baseline BMI of >40 kg/m2 had a 5-fold higher retention (OR 5.53 (CI 1.37, 22.27) p=0.016). CONCLUSION There is a high dropout rate (59%) with only 41% retention in our weight management programme. There may be multiple factors associated with this occurrence. Our study showed that those with known dyslipidemia and those with baseline BMI of more than 40 kg/m2 were more likely to complete the programme and benefit from it.